2021
DOI: 10.3390/jcm10071348
|View full text |Cite
|
Sign up to set email alerts
|

Porous Media Computational Fluid Dynamics and the Role of the First Coil in the Embolization of Ruptured Intracranial Aneurysms

Abstract: Background: The objective of our project was to identify a late recanalization predictor in ruptured intracranial aneurysms treated with coil embolization. This goal was achieved by means of a statistical analysis followed by a computational fluid dynamics (CFD) with porous media modelling approach. Porous media CFD simulated the hemodynamics within the aneurysmal dome after coiling. Methods: Firstly, a retrospective single center analysis of 66 aneurysmal subarachnoid hemorrhage patients was conducted. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Consequently, small amounts of Onyx injected into an aneurysmal sac instantaneously coagulate within the aneurysm [21][22][23][24]24]. The decrease in blood ow velocity in the aneurysm-carrying artery accelerates intraaneurysmal retention of blood, thereby further minimizing the likelihood of Onyx escape.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, small amounts of Onyx injected into an aneurysmal sac instantaneously coagulate within the aneurysm [21][22][23][24]24]. The decrease in blood ow velocity in the aneurysm-carrying artery accelerates intraaneurysmal retention of blood, thereby further minimizing the likelihood of Onyx escape.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, imaging of coils in vivo is limited by the imaging artifacts caused by the presence of the coils themselves. Due to this limitation the majority of CFD studies of coiled aneurysms have relied on naïve porous media assumptions(11, 12, 33, 34) that affect hemodynamic factors in unpredictable ways. (14) While predicting aneurysm recurrence is outside of the scope of this study, Damiano et al(35) demonstrated the potential for predicting aneurysm recurrence using CFD of virtually coiled aneurysms, representing the best attempt to relate post coiling hemodynamics to recurrence to date.…”
Section: Discussionmentioning
confidence: 99%
“…Karol et al utilized porous media computational fluid dynamics (CFD) to determine the reperfusion prediction factor for late-stage ruptured intracranial aneurysms treated with coil embolization. 13 Yasuyuki et al used porous media modeling to predict the recurrence of unruptured cerebral aneurysms after treatment. 14 However, the porous media approach assumes a uniform porosity as the volume density of the coil, which fails to accurately reflect the non-uniform distribution of the coils; ultimately, errors may be introduced in hemodynamic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the method of using porous media is commonly employed to simulate the post‐embolization state of an aneurysm in studies on coil embolization for aneurysms. Karol et al utilized porous media computational fluid dynamics (CFD) to determine the reperfusion prediction factor for late‐stage ruptured intracranial aneurysms treated with coil embolization 13 . Yasuyuki et al used porous media modeling to predict the recurrence of unruptured cerebral aneurysms after treatment 14 .…”
Section: Introductionmentioning
confidence: 99%